PERLINDUNGAN HUKUM BAGI TENAGA KERJA PELAUT DENGAN SISTEM KONTRAK - Dimas Pratama Yuda; Jawade Hafidz (Jurnal Hukum Khaira Ummah, 2019)
The problem of seafarers' protection in the implementation is still far from expectations. This is evident in the employment practices in the maritime field there are still things that are not in accordance with those established in the Manpower Act. Where entrepreneurs still make their own rules for the benefit of the company regardless of what the rights of its workersBased on the results of the study it was concluded that the state protection for maritime workers is still weak and slow from the threat of maritime security and safety. Other issues such as wages, maritime employment contracts, Indonesian maritime profession certification, strikes, unilateral layoffs, severance pay, freedom of association of maritime workers, and foreign seafarers' labor are issues that have hitherto been a problem both from shipping companies and labor Indonesian seafarers. The state must be fair in the payroll system, the internal control function must still have external supervision, the need for ministerial or presidential decree on the standard salary of Indonesian seafarers.Keywords: Legal Protection, Sailors, Contract System